New Nanostructured Silica Adjuvant (SBA-15) Employed to Produce Antivenom in Young Sheep Using Crotalus durissus terrificus and Apis mellifera Venoms Detoxified by Cobalt-60 - Ferreira Junior, Rui Seabra [UNESP]; Anderlini, Renato Pavan [UNESP]; Esteves Sant' Anna, Osvaldo Augusto Brazil; Pimenta, Daniel Carvalho; Orsi, Ricardo de Oliveira [UNESP]; Barraviera, Benedito [UNESP] (Taylor & Francis Inc, 2010)
Equine antivenom is considered the only treatment for animal-generated envenomations, but it is costly. The study aimed to produce Apis mellifera (Africanized honeybee) and Crotalus durissus terrificus (C.d.t.) antivenoms using nanostructured silica (SBA-15) as adjuvant and cobalt-60 (60Co)-detoxified venoms utilizing young sheep. Natural and 60Co-irradiated venoms were employed in four different hyperimmunization protocols. Thus, 8 groups of 60- to 90-d-old sheep were hyperimmunized, enzyme-linked immunosorbent assay (ELISA) serum titers collected every 14 d were assessed clinically daily, and individual weight were measured, until d 84. Incomplete Freund's (IFA) and nanostructured silica (SBA15) adjuvants were compared. The lethal dose (LD50) for both venoms was determined following intraperitoneal (ip) administration to mice. High-performance liquid chromatography on reversed phase (HPLC-RP) was used also to measure the 60Co irradiation effects on Apis venom. At the end of the study, sheep were killed in a slaughterhouse. Kidneys were histologically analyzed. LD50 was 5.97 mg/kg Apis and 0.07 mg/kg C.d.t. for native compared to 13.44 mg/kg Apis and 0.35 mg/kg C.d.t. for irradiated venoms. HPLC revealed significant differences in chromatographic profiles between native and irradiated Apis venoms. Native venom plus IFA compared with SBA-15 showed significantly higher antibody titers for both venoms. Apis-irradiated venom plus IFA or SBA-15 displayed similar antibody titers but were significantly lower when compared with native venom plus IFA. Weight gain did not differ significantly among all groups. 60Co irradiation decreased toxicity and maintained venom immunogenic capacity, while IFA produced higher antibody titers. SBA-15 was able to act as an adjuvant without producing adverse effects. Hyperimmunization did not affect sheep weight gain, which would considerably reduce the cost of antiserum production, as these sheep were still approved for human consumption even after being subjected to hyperimmunization.